Innovation of Stichopus hermanii and HBOT in Increasing the Number of Fibroblasts on Periodontal Ligament - Robbi Akbar Dirmadana; Ghina Sucilia Mediani; I Ketut Ika Sandana; Febryan Alief; Jessica Jenuary Yasin; Arya brahmanta (Denta Journal Kedokteran Gigi, 2017)
Background: The prevalence of malloclussion in Indonesia reached 80% in 2013, accordingly, orthodontic treatment needs also increased. Orthodontic treatment is a treatment to improve the arrangement of teeth. Orthodontic treatment causes movement of the teeth, but this treatment takes quite long time around 15-24 months and it needs an additional therapy to accelerate it.. Fibroblast is a main cell in periodontal ligaments that has an important role on orthodontic tooth movement. Stichopus hermanii (golden sea cucumber) and Hyperbaric Oxygen Therapy (HBOT) can induce fibroblast proliferation. Purpose: To investigate how the innovation of Stichopus hermanii and HBOT can increase the number of Fibroblast in periodontal ligament during orthodontic tooth movement. Materials and Methods: This research used Randomized Post Test Only Control Group Design. The sample involve 30 male adult guinea pigs was randomly divided into 5 groups: negative groups (K-), positive groups (K+), Stichopus hermanii treatment group (P1), HBOT group (P2), and combination group(P3). In K+ and treatment groups, maxillary incisors of guinea pig was placed a helical spring in order to move the teeth to distal. To analyze the number of fibroblast on histology, used Hematoxylin Eosin (HE). Data analysis uses One Way ANOVA, Post Hoc LSD, and Paired T Test. Result: Research data shows an increased average of fibroblast number in the pressure area, K(-): 10,8±0,83; K(+): 9±1,14; P1: 10±1,58; P2: 10,6±1,51; P3: 11±1,41 and in the tension area also experienced an increased average of fibroblast number, K(-): 11,6±1,11; K(+): 12,6±2,88; P1: 14,6±1,14; P2: 16,6±1,14; P3: 18,2±1,92. Conclusion: Innovation of Stichopus hermanii and HBOT increased the number of fibroblast in periodontal ligament during orthodontic tooth movement.